Solubilização de potássio durante lixiviação ácida e básica de siltitos verdes em reatores pressurizados - Safatle, Frederico Amorim (2018)
Potassium (K) is one of the main nutrients in the soil due to its participation in plant growth and in the performance of physiological activities, such as water absorption and circulation of other nutrients in the plant. However, in Brazil, the concentration of K in the soil is scarce due to the high levels of acidity and leaching in the tropical soil and, because of that, it is massively used by the fertilizers industries in its correctives along with nitrogen (N) and phosphorus (P). Contrary to its importance in agriculture, the only potash-producing plant is located in the Taquari-Vassouras Mine, in Sergipe, corresponding to the production of only about 10% of the domestic demand. In this context, potassium has become a strategic element and the pursuit of alternative sources has increased in the last few years. Among the alternative sources in our country, the silicate rock called Verdete stands out, with its reserve located in Cedro de Abaeté/MG and surroundings. Natural Verdete presents contents from 7% to 14% of K2O, which are however, distributed into mineral structures not directly absorbed by the plants. This paper proposes the physical and mineralogical characterization of Verdete as well as the application of hydrothermal treatments using CaCl2.2(H2O), MgCl2.6(H2O), H2SO4 and calcinated CaCO3 in order to extract K+ ions from this mineral. The “Verdete” rock was characterized by granulometric analysis, X-rays fluorescence (XRF) and X-rays diffraction (XRD). It was demonstrated that the rock is enriched with potassium (a content of approximately 11%) and composed by quartz, micas and potassium feldspars. The products obtained from the hydrothermal treatments were analyzed through flame photometry and the results indicated a higher extraction of potassium when reagents such as H2SO4 (maximum of 24% of the fed potassium mass) and the calcinated CaCO3 (maximum of 39% of the fed potassium mass) were used. The XRD analysis of the products showed that the obtained conversion from the reaction with H2SO4 was due to the formation of soluble sulphates, while the reactions between the calcium hydroxide and glauconite, a mineral component of Verdete, promoted the liberation of potassium ions during the treatment carried out with calcinated CaCO3.